POLITIK ANGGARAN DAN EFEKTIVITAS PROGRAM PENGENTASAN KEMISKINAN DI INDONESIA - Putra, Edi; Anjani, Hayatullah; Wahyuni, Yuridah; Alisah, Nur (JURNAL ILMIAH DETUBUYA, 2024)
This study aims to examine the relationship between budget politics and the effectiveness of poverty alleviation programs in Indonesia using a Systematic Literature Review (SLR) approach. Although various studies have addressed the importance of budget allocation and governance, there remains a research gap in systematically integrating the roles of political actors, regional disparities, and institutional capacity in influencing the success of social programs. This study reviews articles from the Dimensions and Scopus databases published over the last ten years (2015–2024), with rigorous selection criteria to ensure the quality and relevance of sources. The findings reveal that weak fiscal allocation, low local institutional capacity, and elitist budget politics contribute to the failure of poverty alleviation programs in many regions. Furthermore, the potential of technology and the health system as instruments for poverty reduction has not been fully realized due to budgetary gaps and unintegrated policies. This research recommends budget reforms grounded in social justice, strengthened institutional capacity, and investments in digital infrastructure and public health as prerequisites for inclusive and sustainable poverty alleviation policies. The study is expected to provide empirical insights for policymakers in designing more adaptive and transformative fiscal interventions.